2014
DOI: 10.1103/physrevb.90.195110
|View full text |Cite
|
Sign up to set email alerts
|

Variational description of the ground state of the repulsive two-dimensional Hubbard model in terms of nonorthogonal symmetry-projected Slater determinants

Abstract: The few determinant (FED) methodology, introduced in our previous works [Phys. Rev. B 87, 235129 (2013) and Phys. Rev. B 89, 195109 (2014)] for one-dimensional (1D) lattices, is here adapted for the repulsive two-dimensional Hubbard model at half-filling and with finite doping fractions. Within this configuration mixing scheme, a given ground state with well defined spin and space group quantum numbers, is expanded in terms of a nonorthogonal symmetry-projected basis determined through chains of variation-af… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 109 publications
(208 reference statements)
0
12
0
Order By: Relevance
“…The calculations presented could in principle be improved in a number of ways: additional symmetries could be broken and restored (such asŜ z or particle number) in the reference configurations; more configurations could be included; and/or a full optimization of all determinants could be performed, in the spirit of the resonating Hartree-Fock approach. 75 The accuracy of any one result can therefore be increased, as shown by Rodríguez-Guzmán et al 76 or by Mizusaki and Imada 77 in the closely related path integral renormalization group (PIRG) approach. Recently, Tahara and Imada 78 have combined the symmetry-projected determinant expansion with short-and long-range Jastrow factors within a variational Monte Carlo framework, which may be used to further increase the accuracy.…”
Section: Multi-reference Projected Hartree-fock (Mrphf)mentioning
confidence: 98%
“…The calculations presented could in principle be improved in a number of ways: additional symmetries could be broken and restored (such asŜ z or particle number) in the reference configurations; more configurations could be included; and/or a full optimization of all determinants could be performed, in the spirit of the resonating Hartree-Fock approach. 75 The accuracy of any one result can therefore be increased, as shown by Rodríguez-Guzmán et al 76 or by Mizusaki and Imada 77 in the closely related path integral renormalization group (PIRG) approach. Recently, Tahara and Imada 78 have combined the symmetry-projected determinant expansion with short-and long-range Jastrow factors within a variational Monte Carlo framework, which may be used to further increase the accuracy.…”
Section: Multi-reference Projected Hartree-fock (Mrphf)mentioning
confidence: 98%
“…Here, we see that for small on-site repulsion U where the system is weakly correlated, CCD is exceptionally accurate, but that it breaks down completely for larger U; 14,15 SUHF, meanwhile, is reasonable but imperfect everywhere. 16,17 In an ideal world, one could simply combine PHF and coupled cluster, but this task is complicated by the very different natures of the two theories. The PHF wave function is concisely written as a (short) expansion in a set of nonorthogonal broken-symmetry determinants, while the coupled cluster wave function is written as a (long) expansion in a set of orthogonal symmetry-adapted determinants.…”
mentioning
confidence: 99%
“…Recently, new results have been reported that are aided by large computing facilities. [25][26][27] These report highly accurate results with the consideration of the spin and spatial symmetry for the Hubbard model as well as qualitatively good results for the selected molecular systems.…”
Section: Introductionmentioning
confidence: 65%